Quantifying the ROI of AI in Hospitals: A Deep Dive into Financial and Clinical Returns - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into the healthcare ecosystem, particularly within hospitals, has rapidly moved from a futuristic concept to a ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care